Embryonic Thermal Manipulation Affects Ventilation, Metabolism, Thermal Control and Central Dopamine in Newly Hatched and Juvenile Chicks - Rocha, Aline C. G. [UNESP] (2021)
The first third of incubation is critical for embryonic development, and environmental changes during this phase can affect the physiology and survival of the embryos. We evaluated the effects of low (LT), control (CT), and high (HT) temperatures during the first 5 days of incubation on ventilation ((Formula presented.) E), body temperature (Tb), oxygen consumption ((Formula presented.) O2), respiratory equivalent ((Formula presented.) E/ (Formula presented.) O2), and brain monoamines on 3-days-old (3d) and 14-days-old (14d) male and female chickens. The body mass of LT animals of both ages and sexes was higher compared to HT and CT animals (except for 3d males). The heart mass of 14d HT animals was higher than that of CT animals. Thermal manipulation did not affect (Formula presented.) E, (Formula presented.) O2 or (Formula presented.) E/ (Formula presented.) O2 of 3d animals in normoxia, except for 3d LT males (Formula presented.) E, which was lower than CT. Regarding 14d animals, the HT females showed a decrease in (Formula presented.) E and (Formula presented.) O2 compared to CT and LT groups, while the HT males displayed a lower (Formula presented.) O2 compared to CT males, but no changes in (Formula presented.) E/ (Formula presented.) O2. Both sexes of 14d HT chickens presented a greater Tb compared to CT animals. Thermal manipulations increased the dopamine turnover in the brainstem of 3d females. No differences were observed in ventilatory and metabolic parameters in the 3d animals of either sexes, and 14d males under 7% CO2. The hypercapnic hyperventilation was attenuated in the 14d HT females due to changes in (Formula presented.) O2, without alterations in (Formula presented.) E. The 14d LT males showed a lower (Formula presented.) E, during hypercapnia, compared to CT, without changes in (Formula presented.) O2, resulting in an attenuation in (Formula presented.) E/ (Formula presented.) O2. During hypoxia, 3d LT females showed an attenuated hyperventilation, modulated by a higher (Formula presented.) O2. In 14d LT and HT females, the increase in (Formula presented.) E was greater and the hypometabolic response was attenuated, compared to CT females, which resulted in no change in the (Formula presented.) E/ (Formula presented.) O2. In conclusion, thermal manipulations affect hypercapnia-induced hyperventilation more so than hypoxic challenge, and at both ages, females are more affected by thermal manipulation than males.